Evaluación de esquemas de parametrización física para el modelado de la altura de la capa de mezcla atmosférica en el Weather Research and Forecasting Model (WRF) v.3. Caso de estudio : Bogotá, Colombia (2017)
The Weather Research and Forecasting Model v. 3.8 was used to simulate mixing heights over the city of Bogota during a 72-hour wet and a 72-hour dry period. For each period, a number of simulations were run, combining different physical parameterization schemes. A modified version of the Holzworth method, also known as the parcel method, was used to calculate the mixing heights for each simulation. These heights were validated using data from daily atmospheric soundings carried out by IDEAM, the official meteorological authority of Colombia. The results of the validation were analyzed in order to suggest which scheme combinations simulated real mixing heights over Bogota more accurately.